STRUKTUR KOMUNITAS MANGROVE DI HUTAN MANGROVE KELURAHAN BELAWAN SICANANG KECAMATAN MEDAN BELAWAN PROVINSI SUMATERA UTARA Mangrove Community Structure in Mangrove Forest, Village Belawan Sicanang, District of Medan Belawan, Province North Sumatera - Yenni Ningsih Siringoringo; Yunasfi Djayus; Desrita Desrita (AQUACOASTMARINE, 2017)
Mangrove forests existed in Village Belawan Sicanang have been many experienced land conversion as embankment and settlements. These conditions led to degradation in habitat quality. The research aimed to know mangrove species composition and to know mangrove community structure. The research took place in May  June 2016. The method used in the determination of the location is purposive sampling and divided into 3 stations based on different activities. Analysis of mangrove vegetation derived mangrove density, relative density, mangrove frequency, relative frequency, dominance, relative dominance, importance value index, diversity index, and evenness index. The results showed that the composition of mangrove species found eleven species of true mangroves that are Avicennia alba, Avicennia marina, Bruguiera gymnorrhiza, Bruguiera hainessii, Ceriops tagal, Nypa fruticans, Sonneratia alba, Sonneratia caseolaris, Xylocarpus granatum, Rhizophora apiculata dan Rhizophora mucronata. The mangrove forest located in Village Belawan Sicanang is classified on very tight criteria where mangrove density ≥ 1500 ind/ha, the relative dominance ≥ 75%, and the mangrove community were in stable condition.Keywords : Mangrove, Species Composition, Community Structure